Chiesa-ordinamento e scienze moderne in Italia - Fattori, Gabriele (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2013)
The tension between sacred and secular runs throughout the history of Italy and determines the Catholic Church’s difficult relationship with scientific progress. However, over the course of time a significant scientific dialogue has been set in motion in the juridical system of the Catholic Church between the theological areas of the humanistic disciplines and the experimental areas of the anthropological sciences. Faced with the progress of modern science, the evolution of canon law therefore becomes a useful and original key to the interpretation of the Catholic Church’s confrontation with modernity.